2021
DOI: 10.15244/pjoes/130636
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Factors in the Investment Prioritization of Facilities Using Recycled PVC

Abstract: There are many types of solid wastes however, plastic wastes are among the ones which have several harmful effects on the environment. Plastic wastes have a long decomposition time in nature and the dangerous chemical compounds in them make them a threat for the environment along with other types of waste. Contamination caused by the plastic wastes attracts worldwide attention nowadays. As a member of thermoplastic polymers family, polyvinyl chloride (PVC) products are one of the most preferred type of plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Among the wide range of methodologies developed throughout the years, the Analytical Hierarchy Process (AHP) is still preferred in recent studies because of its accuracy [29]. AHP has a more than 65% preference rate among authors in the literature [30].…”
Section: Multi-criteria Decision-making Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the wide range of methodologies developed throughout the years, the Analytical Hierarchy Process (AHP) is still preferred in recent studies because of its accuracy [29]. AHP has a more than 65% preference rate among authors in the literature [30].…”
Section: Multi-criteria Decision-making Methodsmentioning
confidence: 99%
“…However, there are no consistency control or group decision aggregation steps embodied in the FAHP algorithm. Hence, in the framework of this study, AHP consistency ratio calculation steps were implemented first to ensure that the consistencies of all individual DM evaluations are satisfied [29,56,65]. Second, calculation steps of the aggregated group decision matrix are added to the FAHP algorithm to propose the F-MCGDM framework that uses TFN and FAHP as the evaluation model of the study.…”
Section: Fuzzy Multi-criteria Group Decision-making (F-mcgdm) Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that chemical recycling incurs a higher cost compared to other recycling processes (e.g., mechanical recycling, incineration), primarily owing to the low value of the recovered products. For example, recycling PVC will generate hydrochloric acid (HCl), and an additional step and cost are required to replace the same . Thus, chemical recycling for PVC might not be a cost-efficient option.…”
Section: Classification Properties and Recycling Of Medical Plasticsmentioning
confidence: 99%
“…It is indicated that the share of these products in relation to all plastic materials produced in the world is 36% [2]. The types of plastics most commonly used in packaging products include: high and low density polyethylene (HDPE and LDPE), polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS) and polyvinyl chloride (PVC) [2,3]. The most commonly used polyethylene, both HD and LD, in Europe accounted for almost 30% of all plastics produced in 2018 [4].…”
Section: Introductionmentioning
confidence: 99%